Harmonizing Economic Growth with Environmental Justice: Circular Manufacturing Pathway (Journal of Economics, Law and Society, 2024)
The global challenge of harmonizing economic growth with environmental sustainability has become a critical issue, particularly within the manufacturing sector. This paper explores the potential of circular economy principles as a pathway to achieving a sustainable manufacturing transition that not only promotes economic development but also ensures environmental justice. By analyzing the synergies and tensions between economic growth, environmental sustainability, and social equity, the paper highlights the role of circular manufacturing in creating resource-efficient, low-waste systems. Key findings show that while circular manufacturing holds substantial potential for enhancing economic growth, job creation, and industrial competitiveness, significant barriers remain, including economic costs, technological gaps, and political and social resistance. Moreover, achieving environmental justice in this transition is essential to ensure that marginalized communities are not disproportionately affected by pollution and waste. The paper emphasizes the need for innovative policies, collaborative governance, and inclusive strategies to overcome these challenges and design equitable supply chains and manufacturing systems. Future research should focus on scaling circular practices across industries, addressing regional disparities, and developing technologies that further reduce the environmental footprint of manufacturing.